ANALISIS PENGENDALIAN PERSEDIAN BAHAN BAKU PADA PABRIK ROTI SARTIKA DISAMARINDA - Ida Rahmawati, Nani Banuwati, Elfreda A. Lau, (EKONOMIA, 2015)
The problem faced in this study is whether the inventory control flour with the calculation of Economic Order Quantity (EOQ) conducted by Bakers Sartika been optimal?The purpose of this research is to know the planning and inventory control of raw materials applied and determine the level of efficiency before and after using Economic Order Quantity (EOQ) and Reorder Point (ROP).Basic Operational Management theories used to focus on the EOQ. Research hypothesis, Inventory Control Flour on Bread Company Sartika been optimal.The analysis tool used is the Economic Order Quantity (EOQ). The analysis showed that the EOQ and ROP suitable to be applied to the Bread Factory Sartika because the calculation of EOQ and ROP is more efficient than the calculation according to the company.Based on the analysis and discussion stated that the Inventory Control flour at Bakers Sartika been optimal. The company supports the hypothesis